Media Pembelajaran Online terhadap Kemampuan Berpikir Tingkat Tinggi Matematika di Tengah Pandemi Covid-19 - Syamsuddin Syamsuddin; Herlina Ahmad; Afriani Afriani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
Covid pandemic 19 conditions that require the learning process between teachers and students to be done from home. This study aims to see whether there is an influence of high-level thinking ability in mathematics through online learning media amid the co-19 pandemic. High-level thinking ability tests or HOTS questions which are the instruments of this research, contain the process of analyzing, evaluating and creating. The results of the research analysis showed (1) the average value of 50.5% pretest while 75.5% posttest (2) one sample t-test analysis test obtained significance of 0.00 <α, and (3) the fulfillment of student activity was in the criterion minimum active is above 75%. Based on the results of the study concluded that the application of online learning media affect the ability to think of high-level students of SMK Mega Link Majene in the midst of a covid-19 pandemic.